Sistema de transporte por Teleférico como vía de acceso entre el Cerro el Cabezón y Megaciudad Señora de Cao, Chicama - Blas Pereda, Thalía Karolay; Vera Salinas, Addirson Fernando; Noriega Vidal, Eduardo Manuel; Rodriguez Beltran, Eduar Jose; Herrera Viloche, Alex Arquímedes; Valdivieso Velarde, Alan Yordan (LACCEI, 2023)
The objective of this research was the design of a cable car transportation system, applying a practical approach. The results were obtained through demand analysis, establishing a capacity of 10 people per trip and an estimated 300 passengers per day. To meet this demand, it was planned to operate with 8 cabins over a 20-year implementation period. Terrain studies revealed that it consisted of poorly graded sand (SP) according to the SUCS classification. A shallow foundation was determined with a minimum allowable load of 1.81 kg/cm2 and a ballast coefficient of 3.66 kg/cm3. The estimated cost of the transportation system is S/. 12,786,574, with an initial investment allocating S/. 4,084,908 for basic infrastructure and S/. 293,373 for the aqueduct. Additionally, annual costs of S/. 127,866 for maintenance and S/. 384,029 for operation of the system are estimated. So far, the total investment cost amounts to S/. 17,676,750. These data reflect the allocation of financial resources and the necessary expenses for the project’s operation. In conclusion, the design of the cable car transportation system provides a solid foundation for future research in terms of its structural design. The obtained results provide relevant information about capacity, costs, and terrain characteristics, which are essential for a successful and efficient project implementation.